Penggunaan Media Pembelajaran Yang Efektif Secara Daring pada Mata Pelajaran Rangkaian Listrik - Muhammad Saseno, Saseno; Ridwan, Muhammad Malik; Alfarizi, Muhammad Rafi; Maulana, Muhammad Irfan; Zulfikar, Lutfi (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2023)
In the present time, online-based learning has become an integral part of modern education, thanks to the advancements in information and communication technology that cannot be denied. However, there are several challenges that have emerged, particularly in the past two years. The global COVID pandemic has necessitated the implementation of online learning. In designing this form of learning, there are several factors that need to be considered. This article will discuss the effectiveness of online learning.